2013
DOI: 10.1074/jbc.m113.489385
|View full text |Cite
|
Sign up to set email alerts
|

Mutating a Conserved Proline Residue within the Trimerization Domain Modifies Na+ Binding to Excitatory Amino Acid Transporters and Associated Conformational Changes

Abstract: Background:The mutation P290R in the excitatory amino acid transporter 1 (EAAT1) causes episodic ataxia type 6. Results: Voltage clamp fluorometry demonstrates changes in the time course of EAAT3 fluorescence signals by the homologous P259R mutation. Conclusion: P259R alters EAAT3 transport functions by decelerating conformational changes associated with sodium binding. Significance: Studying naturally occurring mutations promises identification of unexpected determinants of transporter functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…He carries a heterozygous SLC1A3 missense mutation (RefSeq NM_001166695.1: c.869C>G: p.Pro290Arg) predicting a proline-to-arginine replacement in transmembrane domain 5 (p.P290R) of the human EAAT1 (Jen et al, 2005). EAATs function as both secondary-active glutamate transporters and anion channels (Fahlke, Kortzak, & Machtens, 2016), and we demonstrated that the P290R substitution impairs glutamate transport, but causes gain-offunction of EAAT1 anion channels (Hotzy, Schneider, Kovermann, & Fahlke, 2013;Winter, Kovermann, & Fahlke, 2012). To understand how increased EAAT1 anion currents cause ataxia in EA6 we generated a transgenic mouse model-the Slc1a3 P290R/+ mouse-and demonstrated that excessive chloride efflux in the second postnatal week results in Bergmann glia apoptosis and cerebellar atrophy (Kovermann et al, 2020).…”
mentioning
confidence: 75%
“…He carries a heterozygous SLC1A3 missense mutation (RefSeq NM_001166695.1: c.869C>G: p.Pro290Arg) predicting a proline-to-arginine replacement in transmembrane domain 5 (p.P290R) of the human EAAT1 (Jen et al, 2005). EAATs function as both secondary-active glutamate transporters and anion channels (Fahlke, Kortzak, & Machtens, 2016), and we demonstrated that the P290R substitution impairs glutamate transport, but causes gain-offunction of EAAT1 anion channels (Hotzy, Schneider, Kovermann, & Fahlke, 2013;Winter, Kovermann, & Fahlke, 2012). To understand how increased EAAT1 anion currents cause ataxia in EA6 we generated a transgenic mouse model-the Slc1a3 P290R/+ mouse-and demonstrated that excessive chloride efflux in the second postnatal week results in Bergmann glia apoptosis and cerebellar atrophy (Kovermann et al, 2020).…”
mentioning
confidence: 75%
“…Our clinical and functional data re-inforce the concept that disturbed glutamate homeostasis from genetic variations in SLC1A3 could lead to a broad spectrum of neurological manifestations with overlapping features. The first SLC1A3 mutation (P290R) 8 , arose de novo in a single patient with episodic ataxia, hemiplegia with migraine, and epilepsy, impairs glutamate transport and enhances h EAAT1 anion currents 27 , 32 , likely reducing glial intracellular [Cl − ] 33 , 34 . Another SLC1A3 mutation, found in multiple members of a family with episodic ataxia (C186S), was reported to slightly reduce glutamate uptake levels 9 and to modify intracellular transport of EAAT1 35 , while h EAAT1 anion currents were not studied.…”
Section: Discussionmentioning
confidence: 99%
“…Bipolar cells exhibit a somatodendritic chloride gradient that might serve inversion of GABAergic horizontal cell input (44). We recently reported that a naturally occurring mutation found in a patient with episodic ataxia type 6 modifies the gating of EAAT1 (38,45), resulting in a profound inward-rectification, and we postulated that P290R EAAT1 might affect intracellular anion concentrations in Bergmann glia. The gating of EAAT5 closely resembles gating of P290R EAAT1 anion channels, and it is thus tempting to speculate that EAAT5 might fulfill a similar function in retinal neurons.…”
Section: Discussionmentioning
confidence: 99%